The variation of respiration biomechanics and high resolution computed tomography indices when analyzing chronic obstructive lung disease - E. V. Ekkardt; T. N. Bodrova; F. F. Tetenev; O. V. Rodionova; N. G. Ivanova (Бюллетень сибирской медицины)
The aim of the research was to determine how chronic obstructive lung disease clinical signs with lung ventilation function disturbance to various degrees correspond to respiration biomechanics and high resolution computed tomography indices. It was revealed that respiration biomechanics indices are changed at the early stages of chronic obstructive lung disease formation.